INNOVATIVE APPROACHES TO ELIMINATION OF RISKS IN REAL ESTATE TRANSACTIONS IN TRANSFORMING SLOVAKIA - Spirkova, Daniela (European Scientific Journal, ESJ, 2014)
Slovak Republic is one of the central European countries which economies were centrally planned until 1989. They are mainly economies of all countries of the former socialist block, including Slovakia. The term "transition economies" was emerged at the turn of the 80s and 90s of last century, when gradually they all have decided to leave the path of building socialism. The main characteristic of transition countries is the transition state of their economies - transitive stage - from centrally controlled system to a market economy. Another feature is that this transition involves the transformation of all sectors of the economy, which includes the real estate sector. In transition countries were no real estate market, so small deviations began to move in the same way and to overcome the same problems. Gradually, some of the real estate market became more developed in Hungary and the other in Poland or Slovakia, but in general speaking, the differences were minimal. Real estate markets can be classified according to the degree of maturity divided into developed, developing and emerging. The main differences are mainly in business opportunities, risk and expected return. In this work we deal with a detailed analysis of the risks to the residential property market as well as innovative ways of eliminating them. These are financial instruments that are closely linked with legal requirements, of which some aspects are content of this article.